WAYS TO INCREASE THE AERODYNAMIC EFFICIENCY OF VENTILATION SYSTEMS (British Journal of Global Ecology and Sustainable Development, 2025)
It has been proven that the aerodynamic efficiency of a ventilation system can be increased by reducing aerodynamic losses in the functional units of the supply/exhaust unit, in shaped parts, reducing the speeds in air ducts, etc. If losses in the main branch of a complex ventilation system are minimized, then reducing aerodynamic losses in the branches does not increase its efficiency. There are other ways to increase the efficiency of ventilation systems, which will be discussed in this article.